The Use of High-Dose Omalizumab in the Treatment of Resistant Chronic Urticaria: A Case Series - Altan Ferhatoğlu , Zeynep; Uzunçakmak, Tuğba Kevser; Mutlu, Görkem (Cerrahpaşa Medical Journal, 2025)
Cite this article as: Ferhatoğlu ZA, Uzunçakmak TK, Mutlu G. The use of high-dose omalizumab in the treatment of resistant chronic urticaria: a case series. Cerrahpaşa Med J. 2025, 49, 0012, doi: 10.5152/cjm.2025.25012